Application of triple bottom line concept to artisanal and small-scale mining activities in Wa East District, Ghana - Emmanuel Mensah-Abludo; Kenneth Peprah; Issah Baddianaah (Brawijaya University, 2023)
The artisanal and small-scale mining (ASM) sector offers a supplementary livelihood strategy to agriculture in northern Ghana, acting as a source of capital to support agriculture. However, the sector has been associated with several adverse environmental and socio-economic consequences, making its sustainability dimensions extremely complex and inconclusive across the literature. This study sought to investigate the dynamics of ASM operations in line with the Triple Bottom Line concept. Specifically, the paper explored the influence of the small-scale mining law and institutional framework on ASM operations, examined the relationship between the economic benefits of ASM and other livelihood activities, and assessed the adverse environmental effects of ASM in the host communities. The research design was a mixed method and cross-sectional survey. Household questionnaires, semi-structured interviews and non-participant observation were the main primary data collection techniques. Secondary data were provided by satellite images sourced from USGS Earth Explorer. They were analysed to determine the land cover types. The results indicate that the relevant regulatory state institutions lag behind their law enforcement duty. The ASM is a lucrative job that provides quick income to the youth. However, ASM activities affect food crop farming and decrease the quantity and quality of vegetation causing variations in land cover. Consequently, the host communities and ASM cooperatives have employed some land reclamation strategies. The study recommends increased government support to the relevant regulatory state institutions to constantly monitor and sanitize the ASM sector. To eradicate illegal mining, the study advocates for multi-stakeholder consultation and action.